سير زندگي در بستر قلم : نگاهي به سير نگارشي مارگريت دوراس از خلال دو اثر سد ي براقيانوس آرام و عاشق - زهره ناصحي; راحله مركبي راحله مركبي (Naqd-i Zabān va Adabīyyāt-i Khārijī, 2013)
Many of the avid readers and artists have read Lover, the outstanding work of Marguerite Duras, the French writer, journalist, playwright and director, and have expressed their views through critiques and commentaries. Among other things, they consider this work as Marguerite Duras's auto biography ; while there are those who call it the new novel (nouveau roman). What Duras has written, in fact, which sheds light on her previous pieces of writing, does not fit into any kind of literary genres and emphatically manifests its writer's freethinkingness. Considering A barrier against Pacific Ocean as the basic inspiration of Lover and Duras's style of writing and the changes betrayed after several years of writing gaining experience, it can be concluded that Duras's writing in bespeaking her life has created a recollection-like trend to the extend of transcending the limits and intermingling the reality and myth. The result is projecting and visualizing the buried memories of dark recesses of her mind.